Pengembangan Media Teka-Teki Silang Dengan Talking Stick Untuk Meningkatkan Hasil Belajar Fikih Siswa Kelas V MI Muhammadiyah Kedungwaras - Nisa, Maghfirotun; Miftahul Munif, Moh. Vito (Jurnal Murid, 2025)
Fiqh learning in fifth-grade students at MI Muhammadiyah Kedungwaras is still dominated by one-way lecture methods, resulting in students being less active and learning outcomes not meeting the Minimum Completion Criteria (KKM), particularly on the topic of the sacrifice ritual. This study aims to: (1) determine the process of developing crossword puzzle learning media using talking sticks, (2) determine the feasibility of the developed crossword puzzle learning media using talking sticks, and (3) determine the effectiveness of this learning media in improving student learning outcomes. The study used the Research and Development (R&D) method using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. Data collection instruments included observation, interviews, questionnaires, and pre- and post-tests, with 25 fifth-grade students as participants. The results showed that (1) the development process proceeded systematically through the five ADDIE stages, resulting in media that met students' needs, such as active student involvement in learning. (2) The media's suitability was determined by validation results from media experts at 82.5% and 77.5%, material experts at 80%, student responses at 79%, and teachers at 85%, all of which were considered suitable to very suitable. (3) The media's effectiveness was demonstrated by an increase in the average student score from 64.48 (pre-test) to 86.36 (post-test), and an N-Gain value of 0.64, which fell into the moderate but effective category in improving student learning outcomes.